2014
DOI: 10.1590/s1679-78252014000200006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of nanocomposite laminated structure and its sensibility to modal analysis procedure

Abstract: In this work, tensile and shear modulus, as well as Poisson's ratio of a woven orthotropic nanocomposite plate were determined from vibration data. Plates used in the experiment were 16 layers S2-glass/epoxy composite manufactured by vacuum assisted wet layup. The nanocomposite plate was obtained by adding 0%, 1%, 2%, 5% and 10% nanoclays in weight to the epoxy matrix. A Finite Element model of the composite plate combined with a gradient method was applied to obtain an approximate numerical solution to experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The results reported by Leão et al [20] are consistent with the ones described by Avila et al [21] for nanoclay/epoxy systems, where vibration modes were affected by the nanoclay addition. A later study performed by Duarte et al [22] identified different vibration behaviors based on the amount of nanoclay dispersed and its spatial distribution. The nanoparticles' dispersion into epoxy systems can easily be performed using a high-shear mixer with temperature control.…”
Section: Introductionmentioning
confidence: 98%
“…The results reported by Leão et al [20] are consistent with the ones described by Avila et al [21] for nanoclay/epoxy systems, where vibration modes were affected by the nanoclay addition. A later study performed by Duarte et al [22] identified different vibration behaviors based on the amount of nanoclay dispersed and its spatial distribution. The nanoparticles' dispersion into epoxy systems can easily be performed using a high-shear mixer with temperature control.…”
Section: Introductionmentioning
confidence: 98%
“…These studies are limited to a linear domain. Nanotube, nano-clay, nano-silica and carbon nanotube are the most important nanoparticles that were used in these studies (Ávila et al., 2008; Chandradass et al., 2007; Duarte et al., 2014; Huang and Tsai, 2015; Khan et al., 2011; Rajini et al., 2013; Velmurugan and Balaganesan, 2011). For illustration of the relative researches, several papers were noted afterward.…”
Section: Introductionmentioning
confidence: 99%
“…The impulse hammer technique was used to find natural frequency and damping factor of laminates (Velmurugan and Balaganesan, 2011). In the research of Duarte et al. (2014) tensile and shear modulus, as well as Poisson’s ratio of a woven nanocomposite plate was determined from vibrational data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation